Causes of rutting in flexible and semi-rigid test sections after 14 years of service. Issue 4 (19th May 2018) - Ekblad, Jonas; Lundström, Robert
Abstract : Rutting is a major distress and is commonly targeted in design-build contracts as a key requirement, but at the same time, contemporary design methods usually provide scarce information on evolution in absolute terms. The objective of this paper is to investigate and analyse rutting results from a large full-scale road test. The analyses concerned magnitudes and the causes of rutting with a main focus on flexible and semi-rigid structures: one Reference, one high-performance asphalt (HPA) and one asphalt on a lean concrete (LC) base. Field measurements and sampling for the current study comprised acquiring transversal profiles and coring pavement samples. The results suggest that for the HPA and the LC base pavements, rutting is mainly caused by studded tyre wear and densification of the asphalt layers. For the conventional reference pavement additional rutting, most likely in the lower layers, was noted.